ON A LAME DIFFERENTIAL EQUATION - Piperevski, Boro M. (Matematichki Bilten, 2006)
In this work we consider Lame’s differential equation. With the Hermite polynomial we be obtained formula for one particular solution of a seven class linear homogenous differential equations of the third order with polynomial coefficients.